Intrinsic p53 activation restricts gammaherpesvirus driven germinal center B cell expansion during latency establishment - Shana M. Owens; Jeffrey M. Sifford; Gang Li; Steven J. Murdock; Eduardo Salinas; Darby Oldenburg; Debopam Ghosh; Jason S. Stumhofer; Intawat Nookaew; Mark Manzano; J. Craig Forrest (Nature Communications)
Abstract Gammaherpesviruses are DNA tumor viruses that establish lifelong latent infections in lymphocytes. For viruses such as Epstein-Barr virus and murine gammaherpesvirus 68, this is accomplished through a viral gene-expression program that promotes cellular proliferation and differentiation, especially of germinal center B cells. Intrinsic host mechanisms that control virus-driven cellular expansion are incompletely defined. Using a small-animal model of gammaherpesvirus pathogenesis, we demonstrate in vivo that the tumor suppressor p53 is activated specifically in B cells latently infected by murine gammaherpesvirus 68. In the absence of p53, the early expansion of murine gammaherpesvirus 68 latency greatly increases, especially in germinal center B cells, a cell type whose proliferation is conversely restricted by p53. We identify the B cell-specific latency gene M2, a viral promoter of germinal center B cell differentiation, as a viral protein sufficient to elicit a p53-dependent anti-proliferative response caused by Src-family kinase activation. We further demonstrate that Epstein-Barr virus-encoded latent membrane protein 1 similarly triggers a p53 response in primary B cells. Our data highlight a model in which gammaherpesvirus latency gene-expression programs that promote B cell proliferation and differentiation to facilitate viral colonization of the host trigger aberrant cellular proliferation that is controlled by p53.